TREATMENT OF PATISIRAN IN PATIENTS WHO HAS TRANSTHYRETIN CARDIAC AMYLOIDOSIS (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
Transthyretin amyloidosis, also called ATTR amyloidosis, is associated with accumulation of ATTR amyloid deposits in the heart and commonly manifests as progressive cardiomyopathy. Patisiran, an RNA interference therapeutic agent, inhibits the production of hepatic transthyretin